2014
DOI: 10.1587/elex.11.20140651
|View full text |Cite
|
Sign up to set email alerts
|

Observation of high dielectric constant of Bi-Nb-O<sub>x</sub> thin-film capacitors fabricated by chemical solution deposition process

Abstract: BiNbOx (BNO) thin films fabricated by a chemical solution deposition (CSD) under annealing conditions of 550°C and 20 min were found to exhibit an unprecedentedly high relative dielectric constant of 170, which is substantially greater than that of sputtered BNO films. Transmission electron microscopy analysis showed that the BNO film fabricated by CSD had two crysalline phases, O-BiNbO 4 , cubic pyrochlore, along with amorphous regions. In contrast, the BNO film deposited by sputtering consists of Bi 3 NbO 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Moreover, we found that these BNO films have a cubic pyrochlore structure. [22][23][24] Although it is known that BZN has a pyrochlore structure, such a structure has not been reported for BNO films. 25,26) This finding suggests that a new crystal phase can be formed in BNO films using a CSD method.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we found that these BNO films have a cubic pyrochlore structure. [22][23][24] Although it is known that BZN has a pyrochlore structure, such a structure has not been reported for BNO films. 25,26) This finding suggests that a new crystal phase can be formed in BNO films using a CSD method.…”
Section: Introductionmentioning
confidence: 99%